Examining the functions of the vascular endothelial growth factor/hypoxia-inducible factor signaling pathway in psoriatic arthritis - Yavuz Kiliç,; Derya Guzel Erdogan,; Merve Baykul,; Kemal Nas, (Archives of Rheumatology, 2023)
Objectives: The present study aimed to examine the roles of the vascular endothelial growth factor (VEGF), hypoxia-inducible factor (HIF), and heme oxygenase-1 (HO-1) in psoriatic arthritis (PsA). Patients and methods: In this cross-sectional study conducted between November 2020 and May 2021, 64 patients (43 female, 21 male; mean age: 43.2±10.4 years; range, 22 to 60 years) with active PsA were included in the patient group, and 64 healthy volunteers (43 female, 21 male; mean age: 42.8±10.5 years; range, 23 to 61 years) were included in the control group. The demographic features of all cases were recorded. The following indices were used to assess the activity of PsA: Bath Ankylosing Spondylitis Disease Activity Index, Disease Activity Score in 28 joints (DAS28), and Visual Analog Scale. Additionally, Disease Activity in Psoriatic Arthritis (DAPSA) and Psoriasis Area and Severity Index (PASI) were used to evaluate the patients. The biochemical parameters of the patients were calculated. The serum levels of VEGF, HIF, and HO-1 were determined using an enzyme-linked immunosorbent assay. Results: When the molecule levels and clinical features of the groups were evaluated, it was found that the VEGF and HIF-1 levels were higher in the patient group compared to the control group (p<0.05). No difference was observed in the comparison of the HO-1 levels of the patient group and the control group (p<0.05). A positive correlation was found between VEGF, HIF-1, and HO-1 (p<0.05). A positive relationship was found between VEGF and HIF-1 and erythrocyte sedimentation rate, C-reactive protein, DAPSA score, and PASI score (p<0.05). It was also determined that there was a positive relationship between the HIF molecule and DAS28 (p<0.05). Conclusion: According to the results obtained in the present study, VEGF and HIF play a role in the etiology of PsA, and the observation of intermolecular correlation suggests that these molecules move together in pathogenesis.